Youth Volunteerism Engagement: Are They Ready? - Wei, CHONG Chin; Yen, YUEN Yee; Yen, Wendy TEOH Ming; Chew, GAN Geok; RAHMAN, Muhammad Sabbir (Journal of Posthumanism, 2025)
Volunteerism plays a crucial role in encouraging young people to become active citizens and key agents of positive change within their communities. However, youth often face challenges such as unemployment, social marginalization, exclusion, and limited access to training and opportunities. This paper examines the factors that promote youth engagement in volunteerism. A total of 373 university students participated in the study, and the findings, using PLS-SEM (Partial least squares structural equation modelling), indicate that accessibility, altruism, and utilitarianism positively influence youth volunteerism. Altruism emerged as the most significant motivational factor. This study enhances our understanding of youth engagement in volunteerism and offers valuable insights for educational institutions, government, and non-government organizations to develop effective strategies to promote and support youth volunteerism.